Biological Denitrification Heterotrophe of Water With Fixed Biomass Using Alfa Stems as Energy Source - BELOUANAS-BENBELKACEM, O.; BENRACHEDI*, K. (Asian Journal of Chemistry, 2024)
This work presents the results optimization of the biological process denitrification with fixed biomass using a consumable support (Alfa Stem). In the first part, the influence of hydrolyc and volumic load to value the capacity of nitrate purification in a down flow submerged bio filter was analyzed. Then with an experimental design approach, we have analyzed the qualitative and quantitative aspects of the effects of some factors: concentration of nitrate (80-200 mg L-1) and velocity (0.3-1.0 m h-1) on different responses like the apparent rate of denitrification, as well as concentration of nitrite, nitrate and chemical demand on oxygen in the reactor outlet.